1997
DOI: 10.1209/epl/i1997-00543-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic adhesion between fluid membranes: phase separation and blistering

Abstract: The electrostatically controlled adhesion of giant vesicles on supported membranes is studied by microinterferometry allowing quantitative evaluation of contact formation and surface profile near the contact area. Under suitable conditions the adhesion induced segregation of charged lipids in one of the membranes of contact zone. This leads to patches of tight contact and decoupled blisters, which are demonstrated for the first time. The stabilization of the pressurized blisters is rationalized in terms of cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
42
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 6 publications
4
42
2
Order By: Relevance
“…In a related work, adhesion between cationic vesicles and anionic supported membranes revealed that electrostatic interactions induce lateral charge segregation on the membrane [21,22]. This phase separation leads to patches of tight inter-membrane contact and decoupled "blisters".…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a related work, adhesion between cationic vesicles and anionic supported membranes revealed that electrostatic interactions induce lateral charge segregation on the membrane [21,22]. This phase separation leads to patches of tight inter-membrane contact and decoupled "blisters".…”
Section: Introductionmentioning
confidence: 95%
“…So far, the interplay between lateral phase separation and membrane adhesion has not been considered theoretically in detail except in references [14][15][16]. The work in references [21,22] deals only with the specific case of oppositely charged membranes. In this paper we provide a general phenomenological approach for the adhesion of multi-component membranes.…”
Section: Introductionmentioning
confidence: 99%
“…It also has significant biotechnological importance for the study of DNA association with artificial cationic liposomes [4]. In a recent experimental work on two oppositely charged membranes [5], it is found that the membrane, due to its fluidity, adjusts its area per head in response to the electrostatic interaction. Similar conclusion has been reached by Radler et.…”
Section: Introductionmentioning
confidence: 99%
“…They serve a number of general functions in our cells and tissues [1,2]. Because of its biological importance, the physics of membrane adhesion has received considerable attention both theoretically and experimentally [3,4,5,6,7,8,9,10]. For instance, helper T cells mediate immune responses by adhering to antigen-presenting cells (APCs) which exhibit foreign peptide fragments on their surface.…”
Section: Introductionmentioning
confidence: 99%